2006
DOI: 10.1111/j.1365-2672.2006.02948.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving low water activity and desiccation tolerance of the biocontrol agent Pantoea agglomerans CPA-2 by osmotic treatments

Abstract: Aims:  To study the improvement of tolerance to low water activity (aw) and desiccation during spray drying in Pantoea agglomerans cells subjected to mild osmotic stress during growth. Methods and Results:  The micro‐organism was cultured in an unmodified liquid (control) or in aw‐modified media, and viability of these cells was evaluated on unstressed (0·995) and 0·96 aw stressed solid media, in order to check total viability and aw stress tolerance respectively. Significant improvements in viability on unmod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 49 publications
1
28
2
Order By: Relevance
“…Considering that CPA-8 product was obtained without preconditioning the microorganism to drying and by using non-optimised carriers/protectants and conditions, our results are promising and have the potential to be improved in the future. Studies conducted by Teixidó et al (2006) and Cañamás et al (2008) have demonstrated that the preservation of microorganisms used as biocontrol agents can be improved by induction of desiccation tolerance using different methodologies, such as by growing the microorganisms in a w modified media or under sublethal thermal stress conditions. Bacillus-based products can also be formulated by producing heat-stressed endospores and by using inorganic and organic carriers (Chung et al 2007;Sorokulova et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that CPA-8 product was obtained without preconditioning the microorganism to drying and by using non-optimised carriers/protectants and conditions, our results are promising and have the potential to be improved in the future. Studies conducted by Teixidó et al (2006) and Cañamás et al (2008) have demonstrated that the preservation of microorganisms used as biocontrol agents can be improved by induction of desiccation tolerance using different methodologies, such as by growing the microorganisms in a w modified media or under sublethal thermal stress conditions. Bacillus-based products can also be formulated by producing heat-stressed endospores and by using inorganic and organic carriers (Chung et al 2007;Sorokulova et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This tolerance was attributed to the intracellular accumulation of compatible solutes glycine-betaine and ectoine. The osmoticadapted cells also demonstrated better survival during spray drying, and maintained its biocontrol activity to control green mould of citrus (Teixidó et al 2006). Previously it was explained that pre-harvest application of the antagonist could lead to an improvement in effectiveness.…”
Section: Physiological Improvementsmentioning
confidence: 93%
“…A similar procedure was carried out for the commercial use of the bacterium Pantoea agglomerans (Ewing and Fife) (strain CPA-2) as a BCA (Costa, Usall, Teixido, Delgado, & Viñas, 2002;Costa, Usall, Teixido, Garcia, & Viñas, 2000;Costa, Usall, Teixido, Torres, & Viñas, 2002;Nunes, Usall, Teixido, Fons, & Viñas, 2002;Nunes, Usall, Teixido, & Viñas, 2001;Teixido et al, 2005;Teixidó et al, 2006).…”
Section: Use Of Biocontrol Agents (Bca)mentioning
confidence: 99%